Firm level export dynamics and market access costs: evidence from Kenya - Chacha, Peter Wankuru (School of Economics, 2018)
This thesis examines the process through which firms contribute to variation in Kenya's exports and how a shock to market access costs influences firm dynamics of entry, exit and survival in export markets. The analysis draws on several firm level datasets including: a unique and unexplored panel of transaction level data over the period 2004-2013; a recent census of manufacturing firms; and firms' access to a duty exemptions scheme on imported intermediate inputs over the period 2004-2013. The thesis consists of four main chapters in addition to the general introduction and concluding chapters. The first main chapter (chapter 2) presents the micro level picture of Kenya's exports and unpacks the patterns of export trade for her exporters. The analysis reveals a high degree of exporter heterogeneity in terms of export sales, number of products and number of destinations per exporter as well as a skewed distribution of export sales towards multi-product and multi-destination exporters. A decomposition framework is used to assess the contributions of firm level export adjustments along the extensive and the intensive margins to Kenya's aggregate export growth per year. We find that continuing exporters (firm intensive margin) dominate in contributions to average export growth per year. The contribution of net entry (firm extensive margin) is very small, although at the gross entry level, new entrants outperform exiters. While the overall growth in exports is dominated by the continuing exporters, their export activity is underpinned by significant churning of destinations and products in export portfolios. In particular, there is a lot of experimentation in added and dropped destinations and products. The final section of the chapter examines the performance difference between manufacturing firms that export compared to non-exporters in Kenya. We find that manufacturing exporters are larger in terms of productivity, use more capital per worker, employ more workers, and pay higher wages compared to non-exporters, which is consistent with the findings in the literature from the rest of the world. This provides evidence in support of the fact that exporters contribute to economic growth and improvement of welfare of their workers. The second main chapter (chapter 3) examines the patterns of entry, exit and survival of new exporters in foreign markets, along with the factors associated with their survival in export markets. We find that over the period 2005-2013, the average entry, exit and survival rates for the Kenya's exporters in international markets are 41, 38, and 62%, respectively. These rates are comparable to those documented for exporters in developing countries and represent substantial churning of Kenyan firms through entry and exit from export markets. Looking at the trade characteristics for the exiters, we find that, on average, they are small in export value compared to new entrants and continuing exporters. Furthermore, each cohort of entering firms exhibits a very high exit rate of between 62 and 79% in the first year of entry. Both the proportional hazard approach and panel logit with fixed effects that control for unobserved firm heterogeneity are used in the analysis. Export survival is found to be higher amongst firms with larger product scope; wider geographic scope of exports and larger current export value. This suggests that a firm's own initiative as well as policy interventions to alter these determinants may foster survival and the growth of Kenya's exports. The broad aim in the third main chapter (chapter 4) is to analyse the effect of a specific market access cost, using fragility of a destination market as an exogenous shock resulting in additional costs of entry into markets in Africa and how this alters firm's export behaviour. In particular, we examine the effect of fragility on a Kenyan firm's decision to export to a given destination market in Africa and the role of firm size in mediating the effect of fragility. Our empirical strategy controls for endogeneity of destination choice by the firm through firm-destination country fixed effects such that the effect of destination country fragility on a firm's export decision is identified entirely along the time dimension. The analysis reveals that fragility negatively affects a firms' decision to enter a given destination market, reducing Kenya's bilateral trade through the number of firms willing to export to fragile states in Africa. An increase in a firm's size (or productivity) is found to be key mediation to market access costs, including destination fragility for the Kenyan firms. The results show that larger firms are less adversely affected by fragility and are more likely to become multi-destination exporters to the region compared to small exporters. The chapter ends with an assessment of the effect of fragility on Kenya's export trade margins and shows that the overall effect on Kenya's total exports to a given destination country is negative but insignificant. Fragility reduces the number of exporters and products traded but it increases the average export value for the continuing firms. This latter result is driven by pure selection effect as fragility causes exit of firms that are relatively small. Finally, the fourth main chapter (chapter 5) evaluates the effectiveness of a trade policy incentive provided by the government of Kenya that promotes the use of imported intermediate inputs. Specifically, we examine the performance differences in firm export outcomes for the beneficiaries (treated) relative to the non-beneficiaries (control). Using fixed effects to address potential endogeneity, we find a positive and significant performance premium for the importer-exporters that import intermediate inputs through the scheme relative to the control group. In particular, the importer-exporters who benefit from the incentive outperform non-beneficiaries in export value and geographic scope of exports, but there is no significant difference in the number of products exported. This result suggests that reducing the costs of inputs can help firms overcome market access costs and potentially expand the destination scope of exports that are in turn, positively correlated with survival of firms in international markets.